Association of composite dietary antioxidant index with mortality risk among adults with chronic kidney disease in NHANES - Jun Sun; Haoyu Yang; Aru Sun; Huifang Guan; Weinan Xie; Lin Han; Yu Wei; Xiaoyu Zang; Pengfei Xie; Xiaolin Tong; Yiqun Lin (Scientific Reports)
Abstract At present, the relationship between the intake of antioxidants in food and the mortality rate of patients with chronic kidney disease (CKD), especially the association with the mortality rate of specific causes, is not clear. This study included 6379 adult CKD patients from the National Health and Nutrition Examination Survey (2001–2018). Use the Cox proportional hazards model, restricted cubic spline (RCS) model, and stratified and sensitivity analysis to evaluate the relationship between the Composite Dietary Antioxidant Index (CDAI) and mortality in patients with chronic kidney disease. During the follow-up period, 2381 all-cause deaths were recorded, including 719 deaths from cardiovascular disease, 132 deaths from cerebrovascular disease, and 430 deaths from cancer. We found that compared to the lowest quartile of CDAI, the weighted multivariate hazard ratio of participants in the highest quartile was 0.83 (95% confidence interval: 0.72, 0.96) for all-cause mortality, Cardiovascular mortality was 0.91 (95% confidence interval: 0.70, 1.18), Cerebrovascular death was 0.51 (95% confidence interval: 0.24, 1.07), Death due to cancer was 0.64 (95% confidence interval: 0.45, 0.92). RCS analysis shows a non-linear relationship between CDAI and all-cause mortality and cancer mortality. At the same time, there is no non-linear relationship between CDAI and cardiovascular mortality and cerebrovascular mortality. Stratified analysis shows that race and BMI are influencing factors for CDAI-CKD mortality. Sensitivity analysis confirmed the robustness of the results. Our research findings emphasize the potential advantages of an antioxidant diet in reducing the risk of mortality in CKD patients.